(untitled) (Indian Journal of Animal Production and Management, 2024)
The experiment was aimed to assess the influence of dietary supplementation with probiotic, prebiotic, and synbiotic on the haemato-biochemical profile of SVVU T-17 grower pigs. Twenty-four pigs, aged 2-3 months and with similar body weights, were randomly assigned to four treatment groups: Control (basal diet alone), T1 (basal diet with 0.1% multi-strain probiotic), T2 (basal diet with 0.1% mannan-oligosaccharide prebiotic), and T3 (basal diet with 0.1% synbiotic). Haematological parameters showed no significant differences among the groups (P > 0.05). However, serum albumin levels were significantly (P < 0.01) higher in the T3 group. Both serum cholesterol and triglycerides exhibited significant (P < 0.01) decreases in the treatment groups (T1, T2 and T3) compared to the control group, while total protein and serum glucose remained consistent. In conclusion, synbiotic supplementation demonstrated a positive effect on serum albumin, and all treatments led to a significant decrease in lipid profiles.